Rhizovagine A, an unusual dibenzo-α-pyrone alkaloid from the endophytic fungus Rhizopycnis vagum Nitaf22. Issue 47 (27th July 2020) - Wang, Ali; Zhao, Siji; Gu, Gan; Xu, Dan; Zhang, Xuping; Lai, Daowan; Zhou, Ligang
Abstract : Rhizovagine A (1 ), a dibenzo-α-pyrone alkaloid with a 5/5/6/6/6 fused pentacyclic skeleton and acetylcholinesterase inhibitory activity, was isolated from the endophytic fungus Rhizopycnis vagum Nitaf22. Abstract : Rhizovagine A (1 ), a novel dibenzo-α-pyrone alkaloid with an unprecedented 5/5/6/6/6 fused pentacyclic skeleton, was isolated from the endophytic fungus Rhizopycnis vagum Nitaf22. The structure was elucidated by comprehensive spectroscopic analysis, in combination with quantum chemical 13 C NMR and electronic circular dichroism (ECD) calculations for configurational assignment. A plausible biosynthetic pathway for 1 was proposed. Compound 1 displayed acetylcholinesterase inhibitory activity.